The International Criminal Court, preliminary examinations, and the Security Council: Kill or cure?. (1st October 2021) - Kuhrt, Natasha; Kerr, Rachel
Abstract : In March 2020, the Appeals Chamber of the International Criminal Court (ICC) authorized the Prosecutor to open an investigation into the situation in the Islamic Republic of Afghanistan. This was a significant milestone for the ICC, ending a lengthy and contentious preliminary examination (PE) and opening the possibility of investigation by the ICC of alleged crimes committed by US citizens. By December 2020, four other preliminary examinations were concluded, two of them (Ukraine, UK-Iraq) potentially involving investigation into the conduct of nationals of permanent members of the Security Council (Russia and the UK) and the third (Palestine) involving a close ally of the United States (Israel). While the conclusion of the examinations into the situations in Ukraine, Palestine, and Afghanistan resulted in requests to open full investigations, the outcome in the situation in Iraq-UK was to close the examination with no further steps. This article discusses the situations in UK-Iraq and Ukraine, setting the actions of the ICC Prosecutor and the responses of the P5 members involved in the context of the international and domestic politics of international justice. We argue that, while PEs were and remain highly significant for the future of the Court, they are not the cure to its current malaise.